AYAH, KONTEN, DAN IDENTITAS: STUDI REPRESENTASI FATHERHOOD DI @HOWTODADNZ - Bakti Abdillah Putra (Yayasan Formadana Tabagsel Indonesia, 2025)
The role of father in parenting needs to be involved like a mother does. Not every father is able to follow the action and some children do not have much experience with a father figure or they just feel fatherless. In New Zealand, a father called Jordan Watson appeared to break the stigma that a father has to show off his masculine and strong identity. Jordan shares his contents with the viewers which are related to parenting through Instagram account @howtodadnz. This research is compiled to analyze the representation of fatherhood in that account by elaborating four aspects, such as emotional intimacy, provision, protection, and endowment with qualitative content analysis. The result of research showed that a father can actively stay engaged in parenting. The representation of fatherhood are displayed by the compassion of the the father in giving his time for his children, growing confidence, protecting children from risks, and engaging in positive habit.